International trade : new patterns of trade, production & investment - Grimwade, Nigel, 1949- (Routledge, 2000)
This new edition is a comprehensive account of the most important developments taking place in the world economy and introduces the major economic theories and models emphasizing changes within the world trading system and government responses.